Modularity and neuronal heterogeneity: Two properties that influence in vitro neuropharmacological experiments - Brofiga, Martina; Poggio, Fabio; Callegari, Francesca; Tedesco, Mariateresa; Massobrio, Paolo (Frontiers in Cellular Neuroscience, 2023)
The goal of this work is to prove the relevance of the experimental model (in vitro neuronal networks in this study) when drug-delivery testing is performed. We used dissociated cortical and hippocampal neurons coupled to Micro-Electrode Arrays (MEAs) arranged in different configurations characterized by modularity (i.e., the presence of interconnected sub-networks) and heterogeneity (i.e., the co-existence of neurons coming from two brain districts). We delivered increasing concentrations of bicuculline (BIC), a neuromodulator acting on the GABAergic system, and we extracted the IC50 values (i.e., the effective concentration yielding a reduction in the response by 50 %) of the mean firing rate for each configuration. We found significant lower values of the IC50 computed for modular cortical-hippocampal ensembles than isolated cortical or hippocampal ones. Although tested with a specific neuromodulator, this work aims at proving the relevance of ad hoc experimental models to perform neuropharmacological experiments to avoid errors of overestimation/underestimation leading to biased information in the characterization of the effects of a drug on neuronal networks.